Características da cana-de-açúcar in natura e hidrolisada com cal virgem em diferentes tempos de estocagem - De Rezende, Adauton Vilela (2013)
Our objective was to evaluate the chemical composition and in vitro digestibility of dry matter of hydrolyzed sugar cane in different storage times. We conducted the trial in the Forage Sector at UNIFENAS, campus of Alfenas (MG) in 2010. The data were analyzed as completely randomized design in factorial scheme 2 (sugar cane without lime and hydrolyzed with 1.0% of lime, basis of fresh matter) x 6 (six times of storage: 0, 24, 48, 72, 96 and 120 hours), with three replicates. The sugar cane stored without lime showed lower dry matter (DM), crude protein, neutral detergent fiber and acid detergent fiber contents compared to hydrolyzed sugar cane. However, the hydrolyzed sugar cane showed higher contents of organic matter (OM) and total digestible nutrients. We reported higher in vitro digestibility of DM and OM when the sugar cane was not hydrolyzed. This can be explaining by better chemical composition of sugar cane without lime. The storage of sugar cane without lime shows results more interesting because the chemical composition and digestibility is better than hydrolyzed sugar cane. So, we not recommended using lime on the sugar cane. Moreover, the sugar cane without lime can be stored until 96 hours after cut.